Do students sort themselves based on economic ideology?. (March 2022) - Magee, Christopher
Abstract: This paper describes a classroom experiment that facilitates a discussion of different economic ideologies and of the beliefs held by conservative and liberal economists. The experiment tests whether students tend to associate with like-minded friends more than with students who have different economic ideologies. The results of the experiment suggest that students are closer in ideology to their friends than to other students. The difference in the ideological gap between friends and the gap between random students is statistically significant but is not large in magnitude. The experiment allows the professor to introduce the topic of ideological sorting and its important consequences for individuals in their trust for others and in how extreme their political beliefs become. Sorting can also contribute to confirmation bias, which makes it difficult for students to update their views in response to new information. By discussing ideological sorting in the context of the experiment, professors can help students to improve their ability to seek out and process new information even when it contradicts their previously-held beliefs.